Organizational strategic learning capability: exploring the dimensions. Issue 3 (3rd April 2017) - Moon, Hanna; Sejong, Wendy; Valentine, Tom
Abstract : Purpose: How to build and enhance the strategic learning capability (SLC) of an organization becomes crucial to both research and practice. This study was designed with the purpose to conceptualize SLC by translating and interpreting the related literature to develop empirical dimensions that could be tested and used in a survey instrument. Design/methodology/approach: An instrument was developed to identify empirical dimensions of SLC. The reliability and validity of the instrument were tested. Findings: The resulting survey instrument included 59 items, and 49 remained after empirical test. Based on responses on a five-point performance scale, SLC items were identified and prioritized, and seven dimensions were discovered: external focus, strategic dialogue, strategic engagement, customer-centric strategy, disciplined imagination, experiential learning and reflective responsiveness. Originality/value: The findings of this study extend the knowledge base of multi-disciplines, including strategy management, organizational learning and strategic human resource development (HRD). This study highlights the conceptualization of SLC and importance of the SLC framework in the field of HRD.